Face Context Advantage Explained by Vernier and Separation Discrimination Acuity - Wilson, Hugh R.; Vesker, Michael (Frontiers in Psychology, 2013)
Seeing facial features in the context of a full face is known to provide an advantage for perception. Using an interocular separation perception task we confirmed that seeing eyes within the context of a face improves discrimination in synthetic faces. We also show that this improvement of the face context can be explained using the presence of individual components of the face such as the nose mouth, or head-outline. We demonstrate that improvements due to the presence of the nose, and head-outline can be explained in terms of two-point separation measurements, obeying Weber’s law as established in the literature. We also demonstrate that performance improvements due to the presence of the mouth can be explained in terms of Vernier acuity judgments between eye positions and the corners of the mouth. Overall, our study shows that the improvements in perception of facial features due to the face context effect can be traced to well understood basic visual measurements that may play a very general role in perceptual measurements of distance. Deficiencies in these measurements may also play a role in prosopagnosia. Additionally, we show interference of the eyebrows with the face-inversion effect for interocular discrimination.